3D printing of cell-laden visible light curable glycol chitosan bioink for bone tissue engineering. (1st July 2022) - Chang, Hyun Kyung; Yang, Dae Hyeok; Ha, Mi Yeon; Kim, Hyun Joo; Kim, Chun Ho; Kim, Sae Hyun; Choi, Jae Won; Chun, Heung Jae
Abstract: Although chitosan is the second most abundant natural polymer on earth, with a wide range of biomaterial applications, its poor water solubility limits general printing process. We selected water-soluble methacrylated glycol chitosan (MeGC) as an alternative and prepared a MeGC-based MG-63 cell-laden bioink for 3D printing using a visible light curing system. Optimal cell-laden 3D printing of MeGC was completed at 3% using 12 μM of riboflavin as a photoinitiator under an irradiation for 70 s, a 26-gauge nozzle, a pneumatic pressure of 120 kPa, and a printing speed of 6 mm/s, as confirmed by printability, protein adsorption, cell viability, cell proliferation, and osteogenic capability. In addition, in vitro tests showed that MeGC-70 has a viability above 92%, a proliferation above 96%, and a hemolysis level below 2%. The results demonstrate the potential for MeGC-70 bioinks and 3D printed scaffolds to be used as patient-specific scaffolds for bone regeneration purposes.